How Sustainability Awareness Shapes Consumer Purchase Intentions through Attitudes and Perceived Value in the Thrift Market in Indonesia - Hommy Dorthy Ellyany Sinaga; Hendrian Hendrian (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The fashion industry is a rapidly growing economic sector, but it has a significant impact on the environment. The trend of thrift fashion or buying secondhand clothes has emerged as an alternative form of sustainable consumption that supports the circular economy. This study aims to examine the relationship between sustainability awareness, attitude toward thrift products, perceived value, and consumer purchase intentions in the context of fashion reuse in Indonesia. This study uses a conceptual literature review approach by synthesizing previous research results in the field of sustainable fashion and consumer behavior. The conceptual model is built based on Theory of Planned Behavior (Ajzen, 1991) and Value–Attitude–Behavior Framework (Homer & Kahle, 1988). The synthesis results show that sustainability awareness does not directly influence purchase intention, but rather through two main mediating pathways: (1) positive attitude toward thrift products as an affective pathway, and (2) perceived value towards the functional, emotional, and social benefits of the product as a cognitive pathway. These two mediators explain how environmental awareness shapes behavioral tendencies without the need to involve external variables such as social norms. Theoretically, this study reinforces our understanding of sustainable consumer behavior. In practical terms, the results provide guidance for thrift fashion MSMEs to emphasize sustainability, quality, and ethical image in their marketing strategies in order to encourage more environmentally friendly consumption behavior.